Desenvolvimento e caracterização físico-química de biomembrana de galactomanana e extrato bruto de Allium sativum com potencial efeito modulador da cicatrização de feridas em camundongos - Souza, Regia Karen Barbosa de (2024)
Wounds are a public health issue that generate a significant socioeconomic impact, and new studies aimed at assisting existing therapeutic approaches are essential. Considering that the use of plants for medicinal purposes is a practice that spans millennia and is widely disseminated among the population, this study aims at the development and physicochemical characterization of galactomannan biomembranes and crude Allium sativum extract with potential modulating effect on inflammation and oxidative stress in an excisional wound model in mice. The extract was evaluated for protein, carbohydrate, phenolic compounds quantification, determination of dry mass and moisture, identification of secondary metabolites, and metabolomic profile analysis. The biomembranes were assessed for their swelling capacity, water vapor permeability, and blood compatibility assay. For the evaluation of the modulation of antiinflammatory activity and oxidative stress, an excisional wound was made in Swiss female mice, divided into four experimental groups: Sham (untreated group), biomem21%, biomem35%, and Veic (biomembrane without extract). The animals were euthanized after 2, 7, and 14 days. On the 2nd day, levels of TNF-α, IL-1β, IL-6, IL-10, VEGF, GSH, and MDA were analyzed. On days 7 and 14, samples were dosed for VEGF. The extract showed a content of 0.570±0.020 mg/mL of proteins, 192.642±4.541 mg/mL of carbohydrates, 43,32±3,97 mg GAE/g, 67.68±0.2% moisture, and 32.32±0.2% dry mass. The secondary metabolite tests identified the presence of coumarins, condensed tannins, terpenoids, and steroids. In the metabolomic analysis, it was possible to identify 55 metabolites. The swelling capacity among the biomembranes was evaluated, and there was no difference between biomembranes loaded with or without extract, unlike the water vapor permeability study where the biomembrane without extract had a higher permeability capacity. All biomembranes are hemocompatible. In the DPPH and ABTS+ assay, all filmogenic solutions and the extract possess high antioxidant activity, with biomem21% showing the most effective IC50. The treatments with the biomembranes (21 and 35%) were also able to decrease levels of TNF-α, IL-1β, and IL-6 and increase levels of IL-10 on the 2nd day of treatment. In the growth factor analysis, biomem35% raised VEGF levels, on the 7th day the levels were maintained, and biomem21% showed the greatest increase. On the 14th day, the levels remained and there was no difference between the groups. In the evaluation of antioxidant activity, both treatments raised GSH levels and reduced MDA levels on the 2nd day of treatment, and only biomem21% was able to maintain the protective effect against lipid peroxidation. In summary, the biomembranes showed an important anti-inflammatory and antioxidant effect, and these effects are expected to assist in the healing process.